Study on the Effect of Traditional Chinese Medicine Regulating Intestinal Microecology on AIDS Prevention and Treatment - Zhou, Miao; Liu, Zhiqin; Shang, Yanan (Journal of Contemporary Medical Practice, 2025)
AIDS is a chronic infectious disease in which the human immunodeficiency virus (HIV) violates human T-lymphocytes and destroys the human immune system, and it has been found that T-cells in the gastrointestinal tract are the primary target and the main site of attack of HIV, and that HIV infection affects the micro-ecological balance of the intestine by influencing the number of intestinal bacterial flora and its distribution, and is closely related to the progress of HIV infection. In this paper, the diversity of intestinal flora, the change of intestinal mucosal barrier permeability and integrity, and intestinal immunity of AIDS patients were studied to further explore the protective effects of Traditional Chinese medicine (TCM) on intestinal mucosal barrier and intestinal immunity by regulating intestinal flora, and to clarify the intrinsic mechanism of the multi-targeted and multi-linked effects of TCM on intestinal microecological regulation.